‘값싼 수다(cheap talk)’가 가상적 편의에 미치는 영향 - 최지연 (한국농촌경제연구원, 2013)
‘Cheap talk’ has been proposed to reduce the hypothetical bias in value elicitation mechanisms. This study explores the effect of cheap talk in laboratory experiments by applying three preference elicitation methods; hypothetical ranking, hypothetical ranking with cheap talk, and non-hypothetical choice. Results indicate that the hypothetical willingness-to-pay (WTP) values are higher than non-hypothetical WTPs, however cheap talk was not effective at reducing hypothetical bias.
Keywords: 값싼 수다; 실험선호추출법; 가상적 편의; 지불의사금액; cheap talk; experimental preference elicitation method; hypothetical bias; willingness-to-pay